Black Romeo, White Juliet: The Opportunities of Processing Prejudice in the Works of Shakespeare - Fazekas, Sándor; Dávid, Péter (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2025)
The following study examines the presence of various prejudices in William Shakespeare's plays and their film and stage adaptations. It also attempts to utilize the interpretative yield in a way that can be applied well in drama pedagogy classes. During such classes, students become aware of their own limitations, perhaps even unconscious prejudices, and at the same time gain a deeper understanding of the prejudices against them, their functioning, and their internal logic. The examples of the study come from Romeo and Juliet, The Taming of the Shrew, Othello and The Merchant of Venice; it is important to emphasize that these are prejudices of varying severity, the more serious of which are only recommended for processing from mature adolescence. In such sessions, attention should always be paid to resolving and processing any possible traumas, emotions and conflicts. The world of Shakespeare's dramas can be a great tool for maintaining a distance from personal involvement, as it also approaches the issue of prejudice in a flexible and nuanced way.
Keywords: drama in education; prejudices; Romeo and Juliet; Shakespeare